A case study of Metropolitan Holdings Limited to assess the usefulness of the Global Business Coalition guidelines in relation to workplace HIV/AIDS programmes and a brief examination of the possible impact of the HIV/AIDS disclosure requirements, as recommended by the King II report - Ferreira, Clive Joaquim (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2005.